Circularity in Agri-Food Value Chains in Developing Countries: A Case in Indonesia - Garnevska E; Hidayati DR; McLaren S (MDPI (Basel, Switzerland), 2026)
The adoption of circular economy approaches in agri-food value chains in developing countries remains underexplored, particularly in contexts dominated by smallholder farmers. This paper aims to analyze existing circular practices and identify key barriers to circular transformation in developing country agri-food value chains, with a specific focus on Indonesia. Using a qualitative research design, the study draws on semi-structured interviews, with different value chain players, to empirically examine circularity within the cashew value chain in Indonesia. The findings reveal that while a range of circular practices are undertaken by individual actors across the value chain, these activities remain largely fragmented and weakly coordinated. Key barriers to further circular transformation include limited awareness, economic imperatives, constrained access to appropriate technologies, and insufficient institutional support. Notably, access to finance was not perceived as a major constraint. This study contributes to the literature by providing a multi-actor, value chain perspective on circularity in smallholder-based agri-food systems in developing countries. It offers novel empirical evidence that existing informal circular practices play an important role and should be preserved as value chains modernize. The findings further highlight the importance of stronger vertical and horizontal coordination to scale and integrate circular activities and support a more holistic sustainable transition.
Keywords: circular economy; agri-food; value chain; Indonesia; cashew sector; developing countries